Design of Internet of Things (IoT)-Based Earthquake Detector With Solar Cell Back Up - Firdaus, Muhammad Atha; Rijadi, Bloko Budi; Notosudjono, Didik (Journal of Energy and Electrical Engineering, 2025)
Earthquake detector as an Internet of Things (IoT)-based earthquake detector with solar cell power backup is an innovation to improve the ability to detect earthquakes effectively and in real time. This tool uses a pendulum cone as the main sensor. The way this sensor works is that when an earthquake occurs, the pendulum will move to touch the ring and conduct an electric current to the microcontroller. Earthquake detection data is processed by the ESP8266 microcontroller to provide alarm warnings and send information wirelessly via the Internet network to firebase and then sent to the application on the smartphone. In addition, this tool is equipped with a solar cell as a backup when the main electricity goes out. The test results show that the Internet of Things (IoT)-based earthquake detector can work well according to the design, namely the alarm and notification on the active smartphone when tested. The highest power of the solar panel is on the second day of 8.35 Watts and the lowest power of the solar panel is on the third day of 2.80 Watts. So the design of tools and software can function properly in accordance with the design.